Evaluating the determinants of sugary beverage consumption among overweight and obese adults: An application of the integrative model of behavioural prediction. (February 2018) - Collado-Rivera, Maria; Branscum, Paul; Larson, Daniel; Gao, Haijuan
Objective: The objective of this study was to evaluate the determinants of sugary drink consumption among overweight and obese adults attempting to lose weight using the Integrative Model of Behavioural Prediction (IMB). Design: Cross-sectional design. Method: Determinants of behavioural intentions (attitudes, perceived norms and perceived behavioural control [PBC]) and sugary drink consumption (intentions, skills/abilities, environment and PBC) were evaluated using data collected at a weight loss clinic in a southwestern US city ( n = 338). Determinants of attitudes, injunctive norms, descriptive norms and PBC were evaluated using salient beliefs, which were derived from an elicitation study. Results: Using structural equation modelling, two separate models were evaluated. Both models had good fit (combined model – Comparative Fit Index [CFI] = .970, Tucker–Lewis Index [TLI] = .921, Root Mean Square Error of Approximation [RMSEA] = .062; expanded model – CFI = .966, TLI = .911, RMSEA = .060) and accounted for a significant amount of variance for intentions (40.7%–42%) and sugary drink consumption (16.2%). Conclusion: The IMB appears to be an effective model for planning health education interventions. Health practitioners should operationalise behaviour change techniques and strategies that target attitudes, perceived norms and PBC using the salient beliefs evaluated in this study.